PERAN NILAI – NILAI UKHUWAH PADA PROGRAM TERNAK DESA BERDAYA YAYASAN NURUL HAYAT SURABAYA DALAM PEMBERDAYAAN EKONOMI PETERNAK DI DESA SIDOMUKTI KECAMATAN KEPOH BARU KABUPATEN BOJONEGORO - Imma Mufidatus Sholikhah; Irham Zaki (Universitas Airlangga, 2019)
Nurul Hayat Foundation has several programs, one of which stands out is empowerment program empowered livestock village. In this program Nurul Hayat Foundation works with animal farmers who according to him are able to manage and give birth to healthy livestock. This research uses descriptive qualitative approach. The reason of the researcher using qualitative descriptive approach is to answer the questions that exist in the formulation of the problem comprehensively and deeply about how the role of ukhuwah in the village livestock program empower the Nurul Hayat Foundation Surabaya in empowerment of farmer's economy. The formulation of the problem was answered with data mostly obtained from interviews and observation. The source of data is the qurban animal farmers who cooperate with the Nurul Hayat Foundation Surabaya. The results showed that empowered livestock program at Yayasan Nurul Hayat had an impact on improving the welfare of farmers, this is not apart from applying ukhuwah value in program implementation. Networking, norms, reciprocal relationships and beliefs, the four points based on ukhuwah's value can have a positive impact on the success of the program.Keywords: Empowerment, Ukhuwah Values, Zakah, Infaq, and Shadaqah, Nurul Hayat, LAZNAZREFFERENCESAdi,Isbandi, Rukminto. 2008. Intervensi Komunitas Pengembangan Masyarakat Sebagai Upaya Pemberdayaan Masyarakat. Jakarta:PT. Raja Grafindo Persada.BPS. Survei Penduduk Miskin. Dipetik 4 4, 2018,http:www.bps.go.id/linkTabelStatis/view/id/946:www.bps.go.id/linkTableStatis/view.id.946.Departemen Agama RI, 2002. Al-Qur’an Terjemahan Indonesia. Jakarta: PT Sari Agung.Fauroni, Lukman. 2016. Model Bisnis Berbasis Ukhuwah (studi entitas bisnis pesantren Al-Itiffaq kabupaten Bandung). Skripsi IAIN. SurakartaFirdaus. 2006. Seratus Cerita Tentang Akhlak: Mahabah dan Ukhuwah. Jakarta: Republika.Hadi, Agus Purbathin. 2004. Konsep Pemberdayaan, Partisipasi dan KelembagaandalamPembangunan.Hikmat, Harry.2010. Strategi Pemberdayaan Masyarakat. Bandung: Humaniora Utama Press.Sanrego, Yulizar D, dan Moch. Taufiq. 2016. Fiqih Tamkin (Fikih Pemberdayaan). Jakarta : Qisthi PressShihab, M. Quraish. 1996. Wawasan Al-Qur’an, Bandung : Mizan.Syahra, Rusydi. 2003. Modal Sosial: Konsep dan Aplikasi. Jurnal Masyarakat dan Budaya, Vol. 5, No. 1: 1-20.Undang-undang Dasar Negara Republik Indonesia Tahun 1945.Yin, Robert K. 2009. Case Study Reasearch Design and Methods. Fourth Edition. California: Sage Inc.